Surveillance Urgency to Prevent Village Fund Corruption - Rai Setiabudhi, I Ketut; Arsha Putra, I Putu Rasmadi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 3 (2020), 2020)
This study aims to understand and analyze what is potential for corruption in village funds, and how Prevention Efforts Against Village Funds Irregularities to develop mechanisms and observe symptoms that appear to have a tendency to indicate danger as an effort to prevent irregularities in village funds that can cause losses to the state so it needs to watch out. This study uses normative legal research methods supported by empirical research. In an effort to approach using the statutory approach which has links to issues of financial oversight, corruption, villages and related to the management of village funds. The results of this study are that several things could potentially lead to corruption in village funds that can harm state finances, including the first being the village government's unpreparedness in managing village funds, second is in terms of planning that does not involve the community and the lack of involvement of the Village Consultative Agency, third implementation,  in this case, the implementation of the use of village funds is still many do not follow the existing procedures and the politicization of the budget, and the fourth is accountability. In the case of efforts to prevent misuse of village funds, a preventative effort is needed so that a regulatory regulation is needed to avoid undesirable things that can disrupt and harm state finances.